2010
DOI: 10.1088/0957-4484/21/35/355102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of endocytosis and exocytosis of cationic nanoparticles in airway epithelium cells

Abstract: A major challenge of drug delivery using colloids via the airway is to understand the mechanism implied in their interactions with epithelial cells. The purpose of this work was to characterize the process of endocytosis and exocytosis of cationic nanoparticles (NPs) made of maltodextrin which were developed as a delivery system for antigens in vaccine applications. Confocal microscopy demonstrated that these NP are rapidly endocytosed after as little as 3 min incubation, and that the endocytosis was also fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 38 publications
5
83
0
1
Order By: Relevance
“…The uptake and retention efficiency of the nanoparticles, as well as their intracellular trafficking, also depend heavily on intrinsic cell characteristics, mainly the composition and fluidity of the plasma membrane, and the dynamics of endocytosis and exocytosis. 41 The above data demonstrate the relevance of cholesterol in the plasma membrane to endocytosis of nanoparticles. Plasma membrane cholesterol is a major constituent of caveolae, ie, invaginated regions of the plasma membrane that accomplish caveolin-1-dependent endocytosis.…”
Section: Size and Charged Functional Groups Affect Biocompatibilitymentioning
confidence: 67%
“…The uptake and retention efficiency of the nanoparticles, as well as their intracellular trafficking, also depend heavily on intrinsic cell characteristics, mainly the composition and fluidity of the plasma membrane, and the dynamics of endocytosis and exocytosis. 41 The above data demonstrate the relevance of cholesterol in the plasma membrane to endocytosis of nanoparticles. Plasma membrane cholesterol is a major constituent of caveolae, ie, invaginated regions of the plasma membrane that accomplish caveolin-1-dependent endocytosis.…”
Section: Size and Charged Functional Groups Affect Biocompatibilitymentioning
confidence: 67%
“…Compared with the endocytosis of NMs, exocytosis and intercellular transport of these NMs have been rarely studied. 10 In previous studies, the dependence of calcium, cholesterol, and energy for the exocytosis of some NPs, eg, gold, polysaccharide, and poly(d,l-lactide-co-glycolide), has been reported; [11][12][13] in addition, a study on lanthanide-doped upconverting NPs showed the significance of the microtubule system in NP exocytosis. 10,14 Following exocytosis, intercellular transport of mesoporous silica NPs was evident in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…43 The cationic polymer hydroxycholine was used to coat nanoparticles. After the surface modification, the nanoparticles appeared to be an approximate size of 60 nm.…”
mentioning
confidence: 99%